Argentina : Financial Sector Assessment Program-Financial Safety Nets- Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the financial crisis management and crisis preparedness framework of Argentina. Although Argentina has a well-developed financial safety net that has provided timely support to stressed institutions, the system could be further strengthened. Although the Banco Central de la Republica de Argentina (BCRA) facilities have not been tested, they are well-designed to manage a major banking liquidity crisis. The BCRA should work with other supervisors to monitor potential risks outside its regulatory perimeter. The BCRA approach to supervision is risk-based and focuses on early supervisory action to address deficiencies, but the prompt correction framework could be enhanced.